Pengaruh Pemanfaatan Waktu Luang, Perhatian Orang Tua, Pemberian Reward, Fasilitas Belajar, Kemampuan Berpikir Kritis, Terhadap Prestasi Belajar Siswa Kelas VIII Pada Mata Pelajaran IPS Terpadu di SMP Negeri 1 Sitiung - Ninin Gusmala; Jolianis Jolianis; Mona Amelia (STKIP PGRI Sumatera Barat, 2023)
This study aims to determine the effect of the use of free time , parental attention , giving rewards , learning facilities , critical thinking skills , on the learning achievement of class VIII students in integrated social studies subjects at SMP N 1 Sitiung . This type of research is descriptive associative. The population is 229 people . The sample is 100 people. The instrument used is a closed questionnaire. To determine the effect of the use of free time, parental attention, reward, learning facilities, critical thinking skills partially and simultaneously t test and F test are used. The results of data analysis show that (1) There is a significant effect between the use of free time on learning achievement. VIII grade students of SMPN 1 Sitiung, with a score of 5,510 (2) There is a significant influence between parental attention on the learning achievement of class VIII students of SMPN 1 Sitiung, with a tcount of 6,624 (3) There is a significant influence between giving rewards to class VIII students' learning achievement SMPN 1 Sitiung, with thining 3,147 (4) There is a significant influence between learning facilities on student achievement in class VIII SMPN 1 Sitiung, with tinne 4,533 (5) There is a significant influence between critical thinking skills on student achievement in class VIII SMPN 1 Sitiung , with tcount 4.109 ( 6 ) There is an effect yes There is a significant relationship between the use of free time, parental attention, giving rewards, learning facilities, critical thinking skills on the learning achievement of class VIII students of SMPN 1 Sitiung, with Fcount 91,141. The amount of use of free time, parental attention, reward, learning facilities, critical thinking skills on student achievement of class VIII SMPN 1 Sitiung is 82.9% and the remaining 17.1% is influenced by other factors not included in this study. Keywords : utilization of free time, parental attention, rewarding, learning facilities, critical thinking skills on learning achievement .